SPD response to internal generated neutral to earth transient in low voltage system - Aiza Abdul Adzis, 1981-, author; Noor Azlinda Ahmad, supervisor; Fakulti Kejuruteraan Elektrik (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Sarjana Kejuruteraan (Elektrik - Kuasa)) - Universiti Teknologi Malaysia, 2018